Một số hình thức thuê mua trên thế giới và thực tiễn pháp luật về thuê tài chính ở Việt Nam - Nhung, Doãn Hồng (VNU Journal of Science: Social Sciences and Humanities, 1999)
Nowadays, in our country, the Government and Party are carrying out a reform on many fields of political, socio-economic life. During recent years, the G overn m en t and P a rty havfi h»(>n npplifld an n d vancad fin n n c ia l p rofession in self-activities, especially in financial lease. By virtue of Hnancial lease, the labourforce could be liberated and given opportunities of employment; the manufacturers could be sold their products and at the same time the banks and financial organizations could give the loan effectively. In past time, the financial lease shows step by step its advantages on the safety of the capital in comparison with other credit forms which exist carrying out in Vietnam. In this article, the author would like to introduce to the readers some financial lease forms in the world and to present some ideas on setting up security legal corridor and at the same time o n l i m i t i n g t h e r i s k s i n t h e a p p lie d p ro c e s s of financial lease in Vietnam. The article also desires contributing a small part in the development of financial lease to become a new branch of financial industry of Vietnam in the future